Competition in business of fishing restaurant is highly increasing. In this situation, customer have more better bargaining position. This condition give them opportunity to choose the best one fishing restaurant that give them satisfaction. Therefore, satisfied the customer is the best way to be the winner in the fishing restaurant business competition. This research is aimed to identify attributes of Lumintu 1001 quality of service that influenced the customer satisfaction, to identify the lev - Popong Nurhayati; Ahmad Fahrudin; Dwi Romadhani (Buletin Ekonomi Perikanan, 2007)
Competition in business of fishing restaurant is highly increasing. In this situation, customer have more better bargaining position. This condition give them opportunity to choose the best one fishing restaurant that give them satisfaction. Therefore, satisfied the customer is the best way to be the winner in the fishing restaurant business competition. This research is aimed to identify attributes of Lumintu 1001 quality of service that influenced the customer satisfaction, to identify the level of customer satisfaction toward attributes of Lumintu 1001 quality of service, to get the information of the priority attributes to improve. Result of the research showed 16 attributes quality of service in Lumintu 1001 fishing restaurant. There were sanitary kit, waiter appearance, room layout, room neatness, tasted of food and beverage, atmospheriC of fishing restaurant, suitability of food and beverage, fishing facility, quickness of service, waiter response to the problems, convenience toward payment, friendly of service, availability of foood and beverage written in the list of menu, security of availability of food and beverage, staff skill and knowledge to explain of menu, waiter availability to communication to the customer. Customer assessed attributes of quality of service based on the level of importance and satisfaction each attributes. Customer Satisfaction index showed that quality of service in Lumintu 1001 fishing restaurant gave the satisfaction to the customer. The range of satisfaction is between satisfaction enough to satisfaction. Attributes of quality of service that give priority to improve are quickness of service and room neatness.